Influence of drying method on the crystal structure and thermal property of oil palm frond juice-based bacterial cellulose - Mohamad, Shahril; Abdullah, Luqman Chuah; Jamari, Saidatul Shima; Osman Al Edrus, Syeed Saifulazry; Aung, Min Min; Sy Mohamad, Sharifah Fathiyah (Springer, 2022)
Dehydration of wet bacterial cellulose (BC) mainly focuses on the physical characteristic or mechanical strength, but its polymorph crystal structure and thermal properties were rarely discussed. Herein, this study utilizes the drying method of hot-pressed and freeze-dried to the wet BC to elucidate the BC polymorph crystal structure in correlation with the BC crystallinity and thermal properties. The results indicate that dehydration of BC using hot-pressed (BC-HP) method reduced the cellulose Iα allomorph fraction by ± 5.0%, increased the crystallinity by ± 5.0%, but lower in thermal stability compared to freeze-dried (BC-FD) method. Additionally, BC-HP shows an exothermic reaction of melting at lower enthalpy value which is contradict to BC-FD and plant cellulose that presented an endothermic reaction with higher enthalpy values. Thus, investigation on BC polymorph crystal structure and thermal properties may offer an important role to regulate the desired characteristic of the dried BC.